ANALISIS PENERAPAN SANKSI PIDANA TERHADAP PELAKU TINDAK PIDANA PERDAGANGAN ORANG (STUDI KASUS PUTUSAN PENGADILAN NEGERI MATARAM NOMOR 312/PID.SUS/2020/PN.MTR.) - Vicky Vicky; R. Rahaditya (Jurnal Hukum Adigama, 2022)
Traf icking in persons or human traf icking has now become a public problem that must beimmediately addressed by the government, both central and regional. The problem faced in theresearch is whether the application of criminal sanctions by judges using Article 81 of LawNumber 18 of 2017 concerning the Protection of Indonesian Migrant Workers in the MataramDistrict Court's decision Number 312/Pid.Sus/2020/PN.Mtr is correct? The research method usedis normative juridical law research. The results showed that basically the decision of the MataramDistrict Court Judge Number 312/Pid.Sus/2020/PN.Mtr was correct by imposing criminalsanctions on the accused perpetrators of placing Indonesian migrant workers by individuals underArticle 81 of Law Number 18 of 2017. Refers to the amount of the sanction given only withimprisonment for 8 (eight) months, and a fine of 1 billion, provided that if the fine is not paid, it isreplaced with imprisonment for 2 (two) months each. This is still too light compared to themaximum criminal sanction that can be imposed on perpetrators of a maximum imprisonment of10 (ten) years and a maximum fine of Rp. 15,000,000,000.00 (fifteen billion rupiah). According tothe decision of the Mataram District Court Number 312/Pid.Sus/2020/PN.Mtr. can impose moresevere penalties on the perpetrators of placing Indonesian migrant workers by these individuals,considering that the maximum criminal provisions in the articles imposed are very high, and thepotential for the acts committed will have a large impact.